Indigenous Methods and Pedagogy: Revisiting Ethics in Community Service-Learning (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
This paper looks at the development of a teaching module intended to enhance students’ understanding of ethics in a community service-learning (CSL) class. This module, created to meet academic (western) learning outcomes for CSL, is based upon Indigenous pedagogy and methods, and offers a non-western framing of specific community service goals, particularly reciprocity and transformative dissonance. The paper proposes that moving toward Indigenous or other ways of knowing offers students and instructors an entry point into decolonizing practices and into alternate ways of experiencing service, transformative learning, and power dynamics. The paper also includes a discussion of the theory behind the teaching module and focuses on the intertwining of ethical research protocols (from Tri-Council policy, OCAP® principles, and elsewhere), service-learning goals, and Indigenous methods within the context of settler colonial practices and policies. Alongside other traditional service-learning outcomes, the primary goal of the module is to encourage students to become critical thinkers reflecting on the mechanics of power and social inequity as they experience social justice founded upon the ideals of relationship building.